Efficient competitive equilibria with adverse selection - Alberto Bisin; Piero Gottardi (Center for Economic Studies and ifo Institute (CESifo), 2005)
Do Walrasian markets function orderly in the presence of adverse selection? In particular, is their outcome efficient? This paper addresses these questions in the context of a Rothschild and Stiglitz insurance economy. We identify an externality associated with the presence of adverse selection as a special form of consumption externality. Consequently, we show that while competitive equilibria always exist, they are not typically incentive efficient. However, as markets for pollution rights can internalize environmental externalities, markets for consumption rights can be designed so as to internalize the consumption externality due to adverse selection. With such markets competitive equilibria exist and are always incentive efficient. Moreover, any incentive efficient allocation can be decentralized as a competitive equilibrium.
Keywords: D50; G22; D62; D82; 330; Adverse Selection; Konsuminterdependenz; Versicherungsökonomik; Allgemeines Gleichgewicht; Theorie